The selection effects of part-time work: Experimental evidence from a large-scale recruitment drive - Hyuncheol Bryant Kim; Hyunseob Kim; John Y. Zhu (Federal Reserve Bank of Chicago, 2022)
We implement a field experiment to examine how part-time work attracts applicants with different quality and productivity levels than full-time work. In a large-scale recruitment drive for a data-entry position in Ethiopia, either a part-time or fulltime job opportunity was randomly offered across villages. We find that the parttime work attracts a less qualified pool of applicants with a stronger preference for short work hours, who in turn exhibit lower productivity, all relative to the fulltime work. Our preferred estimates show that this selection effect on productivity may explain up to half of the typical part-time wage penalty. A simple conceptual framework demonstrates that a lack of high quality potential applicants with a strong preference for short work hours could explain the experimental evidence. The results have implications for the selection effects of alternative work arrangements and for the gender pay gap.
Keywords: J22; J24; O15; M51; 330; Part-time work; alternative work arrangements; self-selection; labor productivity; wage-hour relation